Implementation of Oriented Literated Science E-Module to Improve Critical Skills Thinking About in Hydrocarbon Material - Oktari, Bella; Susilawati, Susilawati; Copriady, Jimmi (Journal of Educational Sciences, 2020)
The purpose of this study is to determine the increase in students critical thinking skills after using e-modules oriented towards scientific literacy. This research is a quasi-experimental study using the Design Randomized Control Group Pretest-Posttest. The research sample consisted of 2 classes, namely class XI MIA 8 and XI MIA 10. The analysis results using the independent sample t-test obtained that a significance value of 0.026 <0.05. The results of the analysis of critical thinking skills test data using the N-gain score test for the experimental class obtained a value of 77.2% including the very high category. While the average N-gain score for the control class obtained a value of 55.2% included in the medium category. It can be concluded that there are significant differences in students critical thinking skills in the experimental class with the control class.